Child labour in the Philippines. - Liang, Cheng Lan. (2008)
The objective of this paper is to analyse the supply-side socioeconomic determinants of child labour in Philippines. These determinants are analysed based on data from a national household survey and a labour force survey. The research methodology used is the sequential probit model which assumes that household decisions are made in a hierarchical manner. Using this model, the impact of various household and economic characteristics on the probability of child labour is estimated.